ASSESSMENT OF DIRECTION FOR COORDINATION OF MONETARY REGULATION OF INVESTMENT IN THE INTEGRATION UNIONS - Zelenkevich, Marina; Bandarenka, Natallia (Management and Administration Journal, 2021)
In the context of globalization and regionalization, central banks pursuing monetary policy in the country at the same time become subjects of monetary regulation within the framework of the integrational associations of which they are members. The purpose of the article is to assess the impact of monetary policy on investment and economic growth in integration unions and determine the appropriateness of their coordination. To achieve the goal, a method of correlation-regression analysis is proposed, one which allows for the identifying and assessing of the degree of influence of certain directions of monetary policy of the countries of the integration association on the indicators of investment and economic growth. As a result of the analysis, the expediency of coordination and implementation of a coordinated policy of central banks to stimulate the deposit and credit policy of commercial banks was proved, which positively affects the characteristics of supply and demand in the integrated investment market. The assessment of the directions of the coordination of monetary investments regulation was carried out on the example of an integration association - the Union of Belarus and Russia and can be extended to other integration associations with the participation of Belarus, in particular, to the monetary interaction of countries within the Eurasian Economic Union. The analysis is based on the statistical data of the National Statistical Committee and the National Bank of the Republic Belarus, the EAEU Department of Statistics, as well as statistical information from the Central Bank of Russia and the Union of Russia and Belarus.